مستوى السمات الشخصية لدى طلبة جامعه المرقب ليبيا The level of prominent students' personal traits at the University of Al-Muraqib Libya - Abdulmani, Najah; Al-Hidabi, Dawood Abdulmalek Yahya (2019)
This study aims to identify the most prominent studnts' personal traits of at the University of Al-Muraqeb Libya. Furthermore, it will be attempted to investigate whether there are statistically significant differences in the personal traits of Al- Marqab students according to their gender and specialization. The study population consists of (11366) students and the sample was (374) students from different disciplines. A standardized tool of personal traits was adopted which included 29 items divided into 5 dimensions. Averages, standard deviations, T-test were calculated. The results indicated that there were statistically significant differences for some personality traits based on genders and disciplines.